Polyhydramnios and abnormal foetal heart rate patterns in a foetus with Prader-Willi syndrome: A case report - Tsuyoshi Murata; Toma Fukuda; Aya Kanno; Hyo Kyozuka; Akiko Yamaguchi; Hiromi Shimizu; Takafumi Watanabe; Keiya Fujimori (Elsevier, 2020)
Introduction: Prader-Willi syndrome (PWS) is a complex neurodevelopmental genetic disorder. No definitive clinical signs of antenatal PWS have been identified. Case: A healthy, nulliparous, 29-year-old woman demonstrated polyhydramnios at 27 weeks of gestation. Cardiotocography (CTG) showed an absence of foetal heart rate (FHR) acceleration and moderate FHR variability. Daily CTG demonstrated an absence of FHR acceleration. A male newborn was delivered by caesarean section, weighing 2492 g, which is appropriate for gestational age; the Apgar scores at 1 and 5 min were 6 and 6, respectively, and the umbilical artery pH was 7.295. The newborn exhibited marked hypotonia, lack of sucking, and cryptorchidism. FISH analysis performed due to severe hypotonia showed 46, XY. Ish del (15) (q11. 2q 11.2), which led to the diagnosis of PWS. Discussion: Polyhydramnios and abnormal FHR patterns may be associated with feeding difficulty and hypotonia. These signs may be an indication for antenatal molecular genetic testing to diagnose PWS.